Pendidikan Agama Islam antara Aksi dan Teori: Studi di MI Ma’arif Bego Yogyakarta - Herlina Herlina; M Khoirul Hadi Al-Asy'ari (Islamic Insights Journal, 2019)
This paper is a paper that raises a theme related to the study of Islamic religious education, Islamic religious education between action and theory: the study of the development and implementation of Islamic religious education curriculum (Qur'an Hadith) in Ma'arif Bego Yogyakarta, using a descriptive normative approach there are three important questions how the concept of implementing Islamic education between action and implementation in MI maarif Bego Yogyakarta, the results of this study are an increase in student learning potential and student discussion from the results of the implementation of Islamic education. Paper ini adalah paper yang mengangkat tema terkait dengan kajian pendidikan agama Islam mi, pendidikan agama Islam antara aksi dan teori : studi pengembangan dan imlementasi kurikulum pendidikan agama Islam (Qur’an Hadits) di MI Ma’arif Bego Yogyakarta, dengan menggunakan pendekatan normative diskriptif ada tiga pertanyaan penting bagaimana konsep implentasi pendidikan Agama Islam antara aksi dan implementasi di MI maarif Bego Yogyakarta, hasil penelitian ini adalah adanya peningkatan terhadap potensi belajar siswa dan pertasi siswa dari hasil implemntasi pendidikan Agama Islam. Keywords: MI (Madrasah Ibtidaiyah), Curriculum, Islamic Education.